The Communication Model of Deli Serdang Diskominfostan in Realizing Creative and Innovative Public Information Dissemination - Muhammad Aidil Ghunaya Said; Syukur Kholil (PT Mattawang Mediatama Solution, 2022)
The purpose of this research is to determine how Deli Serdang Diskominfostan's communication model contributes to the creative and innovative dissemination of public information. This study is an example of descriptive qualitative research. The triangulation method was used in this study. Triangulation is a technique for determining the validity of research data. The data for this study came from interviews with several Diskoinfostan members as well as a student. The findings indicate that Diskominfostan's communication model for disseminating public information creatively and innovatively is a one-way communication model, in which Diskominfostan acts as a facilitator for disseminating information to the public or the general public. Instagram, Facebook, YouTube, and radio are examples of public communication media.